The Antibacterial Activity of Bajakah Tampala Extracts (Spatholobus littoralis Hassk.) Mouthwash Formulation Inhibited Dental Plaque against Streptococcus mutans - Rikhaturhohmah; Rospadila Dwi Adrila; Widiya Dwi Handayani; Rasyani; Ananda Alifvia Suprapto; Nofran Putra Pratama; Mitsalina Fildzah Arifah (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Dental plaque is the main cause of dental caries caused by Streptococcus mutans, with a high prevalence in Indonesia. Currently, the mouthwash market contains high levels of alcohol, which can cause long-term side effects. Tampala bajakah root (Spatholobus littoralis) is used in traditional medicine for the Dayak community in Central Kalimantan. Bajakah Tampala root has antibacterial activity produced by flavonoids and phenolic compounds. The development of herbal cosmetics can be achieved by Bajakah Tampala mouthwash formulations to prevent dental plaque caused by Streptococcus mutans infection. In this study, ultrasound-assisted extraction (UBT) and infusion (IBT) derived the active compounds of Bajakah Tampala root extract. The various concentrations of UBT (20–80%) and IBT (10%) were evaluated for antibacterial activity using the disk diffusion method. The results showed that positive control and 80% UBT have antibacterial activity higher than other extracts, with an inhibition zone of 14,01±2,70 mm. Based on these results, an effective mouthwash dosage formulation can be developed at 80% UBT. The formulation evaluation of mouthwash assessed viscosity, homogeneity, pH, and organoleptic test. The UBT mouthwash product has qualified formulation evaluation parameters. This research contributed to the innovation of herbal cosmetics by developing the potential of Indonesian medicinal plants. Keywords: Bajakah Tampala, Antibacterial activity, Mouthwash, Herbal cosmetic, Streptococcus mutans.